The Clay Content Effect on The Formation of Shallow Mole Drainage and The Rate of Lowering Soil Moisture Content - Siti Suharyatun; Bambang Purwantana; Abdul Rozaq; Muhjidin Mawardi (agriTECH, 2014)
Installing shallow mole drainage in the soil is inﬂ uenced by various factors, namely; the physical properties of soil and tools which are used. One of the physical properties of soil that inﬂ uences the formation of the mole drainage is the clay content of soil. This study aimed to explore the condition of the mole drainage formed in paddy soil with different clay contents. The study was conducted in a laboratory scale using a soil bin, a model of mole plough, and soil which was kept homogeneous in the boxes. The experiment was conducted at the Laboratory for Energy and Agricultural Engineering, Agricultural Engineering Department, Universitas Gadjah Mada, Yogyakarta. Mole drainage was installed in 3 paddy soils with different clay content, namely; 13.12% (soil A; loam soil), 41.17% (soil B; clay soil) and 53.36% (soil C; clay soil). The study was conducted by analyzing the geometry of the mole drainage and observing the soil deformation which occurred due to the formation of the mole drainage. The study showed that perfect mole drainages were installed in all of those three types of soil. The mole drainages were quite good and stable with little cracks. Based on the soil crack and ﬁ ssuring of soil, the largest soil deformation has occurred in soil with the highest clay content and the smallest one in soil with the lowest clay content. The characteristics of those three installed mole drainages were almost the same, but they had different effect on the rate of lowering soil moisture content. Here, the mole drainage installed in loam soil is different from which of installed in clay soil. The mole drainage installed in the loam soil did not inﬂ uence the rate of lowering soil moisture content. Contrary, the mole drainage installed in clay soil has effected to increase the rate of lowering soil moisture content.